Pleasure, mind, and soul selected papers in ancient philosophy - Taylor, C. C. W. (Christopher Charles Whiston), 1936- (Oxford : Clarendon, 2008)
C.C.W. Taylor presents a selection of his writings on a set of important topics in the work of some of the greatest ancient philosophers. The central theme of the volume is the moral psychology of Plato and Aristotle, with a special focus on pleasure and related concepts, an area central to Greek ethical thought.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Plato; Aristotle; Pleasure; Ethics; Philosophy, Ancient